LEGAL ANALYSIS ON PRESIDENT REGULATION ON CARBON PRICING IN INDONESIA - Linda Yanti Sulistiawati; Louie Buana (Journal of Central Banking Law and Institutions, 2023)
This paper aims to analyse Indonesia’s new law of carbon pricing namely Presidential Regulation Number 98 Year 2021 on Carbon Economic Value (Presidential Regulation No. 98/2021). The Presidential Regulation is analyzed based on the legal framework for hierarchy in Law Number 12 Year 2011on the Formation of Legislation). This paper found that even though this regulation has fulfilled all the principles stated in the Law on the Formation of Legislation, many details are left to be regulated in the implementing regulation (as indeed requested in the Presidential Regulation), and more clarification needed for the roles of each actors and stakeholders in carbon economic value and how carbon economic value will invite public participation in its implementation.